Rancang Bangun Square Wave Full-Bridge Inverter Untuk Pembangkit Listrik Tenaga Angin Mikro - Didi Istardi; Agus Wirabowo (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
The simple principle of wind power plant is use wind as main exciter to rotate the turbine. The turbine convert wind to electric energy. The output signal is alternating (AC) current. This current was changed to direct current (DC) by rectifier circuit. The DC current was used as charge the energy storage, battery. Next step, the DC current from battery convert to AC current using inverter circuit. The result of inverter shows that the error is 20% with 240V no load.